Calculation of electrical energy in asymmetric modes in three-phase networks - Dehtiar, Yaroslav (National Technical University "Kharkiv Polytechnic Institute", 2024)
Research focuses on improving methods of accounting for electric energy in three-phase networks during asymmetric conditions. It explores direct metering methods based on voltage and current measurements in each phase, as well as the development of mathematical models for analysis. The scientific novelty lies in the prediction and development of advanced devices utilizing sensor, microprocessor, and communication technologies to ensure accurate energy accounting in all phases and network conditions.
Keywords: electric energy accounting; three-phase networks; direct metering methods; mathematical modeling; microprocessors; communication; energy management